Two terrorists' meet - Psinakis, Steve (California : Alchemy Books, 1981)
Contemporary usage of the word "terrorist" conjures an image of a young man or woman whose face is hidden by a ski mask, a submachine gun in one hand and a grenade in the other, holding some innocent people hostages to his or her arrogant demands.
Part I. The meeting -- Part II. The dialogue.
Keywords: POLITICAL ISSUES